A solvent 'squeezing' strategy to graft ethylenediamine on Cu3(BTC)2 for highly efficient CO2/CO separation. (20th July 2018) - Zhong, Ruiqin; Yu, Xiaofeng; Meng, Wei; Han, Songbai; Liu, Jia; Ye, Yunxing; Sun, Changyu; Chen, Guangjin; Zou, Ruqiang
Graphical abstract: A novel solvent 'squeezing' strategy is reported to graft basic ethylenediamine molecules into porous MOF materials for high efficient CO2 /CO separation. Highlights: A novel solvent squeezing method to graft ethylenediamine (ED) on Cu3 (BTC)2 is reported. The ED-grafted MOF prepared by solvent squeezing method shows excellent CO2 /CO selectivity. Theoretical calculation of interactions between CO2 or CO and ED-grafted MOFs was carried out. Abstract: Highly efficient separation of residual carbon dioxide (CO2 ) from syngas, mainly composed of carbon monoxide (CO) and hydrogen (H2 ), could not only make its utilization more energetically efficient but also avoid catalysts poisoning in some industrial applications. In the attempts to address this issue, it is acknowledged that CO2 /CO separation is the vital step since H2 is a nonpolar molecules, difficult to be polarized and could be easily separated from CO2 . Herein, we report a novel strategy to graft basic ethylenediamine (ED) molecules onto porous metal–organic frameworks (MOFs) as solid adsorbents for CO2 /CO separation via solvent 'squeezing' approach, in which Cu3 (BTC)2 (BTC = 1, 3, 5-benzenetricarboxylate) MOF was employed as the pristine MOF. Surprisingly, the ED-grafted Cu3 (BTC)2 shows unprecedented enhancement of CO2 /CO selectivity of 226% at 273 K and 861% at 298 K, respectively, in comparison with the solvent-free Cu3 (BTC)2 . Moreover, despite the large isosteric heats of adsorption of CO2 on the ED-grafted Cu3 (BTC)2, it could be easily regenerated at moderate temperature. This work provides an efficient and facile method to functionalize MOFs for CO2 capture.